Multimedia Interaktif untuk Meningkatkan Motivasi dan Hasil Belajar IPA Materi Struktur Organ Tubuh Manusia - Dinar Arena Tiari; Suharno Suharno (EduBasic Journal: Jurnal Pendidikan Dasar, 2019)
The application of interactive multimedia is important to enhance learning motivation and outcomes of elementary scchool students. Science material is assumed as difficult and percieved as lack motivational subject. The purpose of this study was to (1) improve student motivation through the application of interactive multimedia in science for fourth grade of Brubuh 2 Elementary School; (2) improve student learning outcomes through the application of interactive multimedia in science for fourth grade of Brubuh 2 Elementary School. This research is a classroom action research (CAR) with the research subjects were 21 students of fourth grade of Brubuh 2Elementary School. The results showed that an increase in student learning outcomes, including an increase in the average grade of 60.38% in pre-cycle into 72.41 % in the first cycle and 83.09% in the second cycle. The percentage of student motivation toward science learning by using interactive multimedia application amounted to 67.43% in the first cycle and increased to 84.23% in the second cycle. The second variable of this class action research has qualified research success criteria, that is motivation and completeness learning outcomes of students reached 80 %. This claimed that the interactive media is acceptable to enhance the motivation and science learning outcomes.